JURIDICAL REVIEW OF THE EFFECTIVENESS OF LEGAL AID PROVISION BY ADVOCATES THROUGH DIGITAL MEDIA - Ismaidar; Sayaharani, Nabilah; Nurdiana, Citra; Saputra, Defri Dwi; Haharap, Rizki Nanda Fauzi (JILPR Journal Indonesia Law and Policy Review, 2025)
The rapid advancement of technology in Indonesia has catalyzed transformation across various sectors, including the provision of legal aid services by advocates. This study investigates the effectiveness of delivering legal aid through digital media from a juridical perspective, with particular emphasis on the opportunities and challenges associated with its implementation. Employing a normative juridical approach, the research examines the legal frameworks regulating digital legal aid practices, notably the Advocate Law, the Electronic Information and Transactions (ITE) Law, and the Advocate Code of Ethics. The findings indicate that digital media can significantly enhance the accessibility of legal services, particularly for communities in remote areas. Nevertheless, the implementation of digital legal aid faces persistent challenges, including the absence of specific regulatory provisions, concerns over data security, and disparities in digital infrastructure. Advocates providing online legal services may be classified as Electronic System Providers and are thus obliged to comply with the provisions of the ITE Law, especially those relating to data protection and the security of electronic transactions. The study concludes that comprehensive regulatory reforms are essential to govern the practice of digital legal aid effectively, alongside efforts to improve digital infrastructure and literacy. Key recommendations include the development of technical guidelines for digital legal aid delivery and the reinforcement of data security systems to safeguard clients’ interests.